2019
DOI: 10.1007/s12192-019-00978-0
|View full text |Cite
|
Sign up to set email alerts
|

l-Thyroxine induces thermotolerance in yeast

Abstract: The cellular stress response (CSR) is a universal inducible reaction modulated, among others, by heat, drugs, and hormones. We aimed to investigate the role of L-thyroxine (T4) on the heat shock (HS) response in Saccharomyces cerevisiae. The CSR was evaluated by determining growth and viability of post-logarithmic phase grown yeast cultures after HS at 53°C for 30 min. We found that long-term T4 exposure can induce a dose-dependent and Hsp90 and H + trafficking-related thermotolerance in yeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…T4 enhanced thermotolerance in yeast. Nonionizing radiation, such as WiFi connection, may modify the morphology and expression of genes that encode heat shock proteins (Hsp) in the thyroid gland, or the two different thyroid hormone receptor (TR) types can act as oncogenes or as tumor suppressor genes in human cancer. Furthermore, the thyroid hormone protects cardiomyocytes from H 2 O 2 -induced oxidative stress via the phosphoinositide 3-kinase (PI3K)-protein kinase B (Akt) signaling pathway, whereas hypothyroidism and hyperthyroidism have different effects on heart function. , …”
Section: Introductionmentioning
confidence: 99%
“…T4 enhanced thermotolerance in yeast. Nonionizing radiation, such as WiFi connection, may modify the morphology and expression of genes that encode heat shock proteins (Hsp) in the thyroid gland, or the two different thyroid hormone receptor (TR) types can act as oncogenes or as tumor suppressor genes in human cancer. Furthermore, the thyroid hormone protects cardiomyocytes from H 2 O 2 -induced oxidative stress via the phosphoinositide 3-kinase (PI3K)-protein kinase B (Akt) signaling pathway, whereas hypothyroidism and hyperthyroidism have different effects on heart function. , …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we investigated whether triiodothyronine could affect other proteins. Interestingly, it was shown that L-Thyroxine (T4) can enhance thermotolerance in yeast [11]. Hsp90 was selected as a cellular stress marker that forms a broad interactome of the cellular proteome.…”
Section: Introductionmentioning
confidence: 99%